Combined deletion of Xrcc4 and Trp53 in mouse germinal center B cells leads to novel B cell lymphomas with clonal heterogeneity. Issue 1 (December 2016) - Chen, Zhangguo; Elos, Mihret; Viboolsittiseri, Sawanee; Gowan, Katherine; Leach, Sonia; Rice, Michael; Eder, Maxwell; Jones, Kenneth; Wang, Jing
Abstract Background Activated B lymphocytes harbor programmed DNA double-strand breaks (DSBs) initiated by activation-induced deaminase (AID) and repaired by non-homologous end-joining (NHEJ). While it has been proposed that these DSBs during secondary antibody gene diversification are the primary source of chromosomal translocations in germinal center (GC)-derived B cell lymphomas, this point has not been directly addressed due to the lack of proper mouse models. Methods In the current study, we establish a unique mouse model by specifically deleting a NHEJ gene, Xrcc4, and a cell cycle checkpoint gene, Trp53, in GC B cells, which results in the spontaneous development of B cell lymphomas that possess features of GC B cells. Results We show that these NHEJ deficient lymphomas harbor translocations frequently targeting immunoglobulin (Ig) loci. Furthermore, we found thatIg translocations were associated with distinct mechanisms, probably caused by AID- or RAG-induced DSBs. Intriguingly, the AID-associatedIg loci translocations target eitherc-myc orPvt-1 locus whereas the partners of RAG-associatedIg translocations scattered randomly in the genome. Lastly, these NHEJ deficient lymphomas harbor complicated genomes including segmental translocations and exhibit a high level of ongoing DNA damage and clonal heterogeneity. Conclusions We propose that combined NHEJ and p53 defects may serve as an underlying mechanism for a high level of genomic complexity and clonal heterogeneity in cancers.